Public health and economic outcomes tradeoffs during the COVID-19 pandemic: political perspectives - Huan Huu Nguyen; Vu Minh Ngo; Uyen Hoang Dinh Nguyen (Cogent Economics & Finance, 2024)
This comprehensive study delves into the nuanced relationship between public health initiatives, particularly non-pharmaceutical interventions (NPIs), and their economic repercussions amid the COVID-19 pandemic. Employing a dataset spanning from February 2020 to June 2021, this study conducts a comprehensive analysis of the interplay between democracy, Nonpharmaceutical Interventions (NPIs) and economic outcomes, with a particular focus on unemployment rates. The research findings indicate a nuanced interaction between democracy and the implementation of NPIs, suggesting that democratic contexts do not only enhance the NPI measures' overall efficacy in curbing the pandemic but also preserve economic stability, particularly by mitigating the adverse effects on unemployment rates. Thus, nations with their robust economic reserves and democratic infrastructures, have effectively employed NPIs to protect public health while mitigating economic downturns, aligning with the 'Zero-COVID' strategy. The study also presents a compelling argument that nations under economic strain can still benefit from NPIs, provided they operate within a democratic framework. This assertion is supported by evidence suggesting that democratic governance plays a pivotal role in the effective implementation of NPIs, facilitating both health crisis management and economic stability. This study explores the complex relationship between nonpharmaceutical interventions (NPIs) and their economic impact during the COVID-19 pandemic, particularly focusing on how democratic governance influences this dynamic. Using data from 50 countries over 17 months, the paper demonstrates that NPIs, such as lockdowns and social distancing, effectively mitigated the spread of COVID-19. Importantly, it reveals that democratic nations, due to their governance structures, were better equipped to balance public health imperatives and economic stability, especially in mitigating unemployment. The research emphasizes the critical role of democracy in ensuring effective implementation of NPIs while reducing the adverse economic consequences. The significance of this work lies in its contribution to understanding how different governance models influenced pandemic management. By offering insights into the interplay between health and economic outcomes, the findings provide valuable lessons for policymakers, especially in the context of managing future public health crises. The study also challenges the perception that public health and economic objectives are mutually exclusive, instead advocating for a more integrated approach that ensures both health preservation and economic resilience.
Keywords: A14; I15; I18; 330; COVID-19; democracy; nonpharmaceutical interventions; public health policy; unemployment